(untitled) (JISTECH: Journal of Information Science and Technology, 2023)
The Yield of a photoreduction process of chromium(VI) or Cr (VI) catalyzed by ZnO semiconductor structured in the zeolite/ZnO-zeolite (ZnO-Z) can be influenced by several factors, including the exposure time and the initial concentration of the Cr (VI) solution. In this study, the photoreduction process of Cr (VI) is carried out in a closed batch reactor equipped with a magnetic stirrer and a 38 Watt UV lamp. A total of 50 mL of a Cr(VI) solution and 25 mg of ZnO-Z was used to study the effect of exposure time and the initial concentration of the Cr(VI)solution to the yield of its photoreduction process. The concentrations of Cr (VI) were determined by UV-Vis spectrophotometer using difenilkarbazid method. To determine the catalyst performance of ZnO-Z in the photoreduction process, an examination of the catalyst in the form of bulk ZnO (ZnO bulkform) has been done. The results showed that the optimum exposure time in the photoreduction process of Cr (VI) catalyzed by ZnO-Z is 25 hours and the optimum initial concentration of Cr (VI) is 25 mg/L. Photoreduction yield of Cr (VI) by catalyst ZnO-Z is higher than the ZnO bulkform.